Case: Unusual Migration of Osteosynthetic Material - Petr Habal; Václav Málek; Josef Novotný (Acta Medica, 2005)
The authors present a rare and unusual case of complication, migration of osteosynthetic material for stabilization, titanium rod, which was used for stabilization of comminutive fracture of the first lumbar vertebra. This rod migrated from the retroperitoneal space to the pleural cavity. The removal of this rod was carried out by videothoracoscopy.